UJI KINERJA MARSHALL AGREGAT BANTAK MERAPI DENGAN MENGGUNAKAN SERAT POLYPROPYLENE - Faqih Ma’arif, Pramudiyanto (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2014)
This research aim to describe of polypropylene and characteristic Optimum Marshall using Bantak Merapi as agregate in the proportion mix. The method used experimental laboratory. The research consist of four varians, that are A (0% PF); B (0,1% PF); C (0,3% PF); and D (0,5% PF), with PF is Polypropylene fibers. The kind of testing are Stability test; penetration test; softening point; flash point and dencity test. Data analysis used descriptive quantitative. Test result showed that the optimum polypropylene fibers is 0,3%; the amount of density; void in mix (VIM); stability; and flow were the result 2,16gr/cm3; 10,85%; 819,03kg; and 2,23mm.Key words: Polypropyelene fibers, Bantak